A clinical outcomes and cost analysis comparing photoselective vaporization of the prostate to alternative minimally invasive therapies and transurethral prostate resection for the treatment of benign prostatic hyperplasia. - Stovsky, MD; Griffiths, R; Duff, S (2006)
PURPOSE: We critically evaluated the clinical outcomes and cost characteristics of alternative procedural treatment options for symptomatic benign prostatic hyperplasia. MATERIALS AND METHODS: An outcomes and cost analysis was performed for benign prostatic hyperplasia treatments, including photoselective vaporization, microwave thermotherapy, transurethral needle ablation, interstitial laser coagulation and transurethral resection. Clinical outcomes were measured by the percent improvement in American Urological Association/International Prostate Symptom Score, the maximum uroflowmetry rate and quality of life score. An economic simulation model was constructed to estimate the expected cost of benign prostatic hyperplasia procedural therapies from a payer perspective. The model included costs of initial treatment, followup care, adverse events and re-treatment. Sensitivity and threshold analyses tested the impact of changing model inputs on base case results. RESULTS: Ablative therapies showed better improvement in symptom score, flow rate and quality of life score compared to thermotherapy procedures. Photoselective vaporization resulted in the largest beneficial changes in American Urological Association/International Prostate Symptom Score, the maximum uroflowmetry rate and the quality of life score at all time points evaluated, followed by transurethral resection and then interstitial laser coagulation. The estimated cost was lower for photoselective vaporization than for any other procedural option at any interval studied. Sensitivity analyses indicated that the results of baseline analyses were robust to reasonable changes in clinical and economic inputs to the model. CONCLUSIONS: Compared to alternative treatment options photoselective vaporization of the prostate is a clinically efficacious and cost-effective treatment for symptomatic benign prostatic hyperplasia.